Low-grade endometrial stromal sarcoma presenting as vaginal nodule - Corpa, Marcus V.N.; Serafini, Eduardo P.; Bacchi, Carlos E. [UNESP] (Elsevier, 2004)
Endometrial stromal sarcoma is a rare neoplasm of the uterus. Extrauterine locations of this neoplasm, excluding metastases or local extension, are even more unusual and are usually associated with the presence of endometriosis. The authors report a case of endometrial stromal sarcoma presenting as a vaginal wall nodule, without any sign of primary uterine tumor after extensive evaluation or presence of endometriosis. The morphology, immunohistochemical profile, differential diagnoses, and pathogenesis are discussed, as well as a review of the literature on this issue. © 2004 Elsevier Inc. All rights reserved.
Keywords: CD10; Endometrial stromal sarcoma; endometriosis; vagina; adult; anamnesis; cancer tissue; case report; cell nucleus; curettage; cytology; cytoplasm; echography; endometrium sarcoma; female; follow up; human; hysterectomy; laboratory test; medical assessment; microscopy; mitosis; necrosis; pelvis; priority journal; sample; spindle cell; staining; surface property; tumor cell; tumor recurrence; tumor volume; uterus tumor; vagina tumor; Adult; Antigens, CD; Diagnosis, Differential; Disease-Free Survival; Endometrial Neoplasms; Female; Humans; Immunohistochemistry; Receptors, Estrogen; Receptors, Progesterone; Sarcoma, Endometrial Stromal; Semaphorins; Tumor Markers, Biological; Vaginal Neoplasms